Feasibility Analysis of Wind Power Plant in South East Region, Vietnam - Truong, Nguyen Tuong An; Khanh, Nguyen Binh; Giap, Luong Ngoc; Trung, Bui Tien; Le, Ngo Phuong; Vinh, Tran The (Engineering, Technology & Applied Science Research, 2024)
The wind power market is expanding quickly and the cost of wind power equipment is decreasing, making wind power technology a key player in the world’s energy transition. Assessing wind potential and selecting the right wind turbine site are crucial parameters for developing a wind farm. Vietnam focuses on onshore and nearshore wind power projects due to its promising wind power potential and supportive policies. However, Vietnam has diverse climate characteristics and wind patterns. Therefore, initial basic research is necessary to evaluate the feasibility of investing in wind power projects. This study examines the technical feasibility of a typical wind power project in the Southeast region of Vietnam using Wind Atlas Analysis and Application Program (WAsP) software. The results indicate that the wind turbine’s type and installation location significantly affect wind power plants’ efficiency. The total power output of the wind power project after factoring with losses at a rate of 17%, is 304,149 MWh.